A Study on Investor Perception About Systematic Investment plan (SIP) in the city of Mumbai. - Aurora, Rajinder S. (Gyan Management Journal, 2020)
Systematic investment plan (SIP) has emerged at alternative investment plan for large number of investors interested in high returns but less risk with investments made gradually in Mutual Funds & Stocks. The study aims is to find out the factors that motivate investors to invest in systematic investment plan and the problem they face in this scheme. A sample of 100 respondents who invest through SIP belonging to the commercial Capital of India - Mumbai in Maharashtra has been taken for the purpose of the study. The data has been collected from primary sources using a questionnaire evolved for this study. The collected data has been analyzed using various statistical tools. Results of the study found that for higher return with low risk the investors are motivated to invest in systematic investment plan. The study also concluded that knowledge and operational platform is one of the main barrier that investor are facing of scheme.